Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{5x+y^2}{x^2y}-\frac{5y-x^2}{xy^2}\)
\(=\frac{y\left(5x+y^2\right)-x\left(5y-x^2\right)}{x^2y^2}\)
\(=\frac{5xy+y^3-5xy+x^3}{x^2y^2}\)
\(=\frac{x^3+y^3}{x^2y^2}\)
P = x(x - y) - x + y2(x - y) - y2 + 5
P = x - x + y2 - y2 + 5
P = 5
Q = x2(x - y) - x2 + y2(x - y) - y2 + 5(x - y) - 2015
Q = 5 - 2015
Q = -2010
=23445677765666667869567687668768676864786328652156191568129635912659129115767668219635198669175612876575555555654364396663676478296934986327698761963982369639874689326892346985983456937569236984698469262332948692022709247209762297534906745677902620346736776--66776236-3676767766476379667347967672364764767233093276766907676707672078747498087907997479439703473470340777360970790237443767437347672476743720674770247702934670934709324740709672367243676767234+relk;jdslgkjgr;ljgkljdslkjglkgdsfhadagkkgakhasghjgjhagjhgajhgfjhgkjkkjjkjkhhhkhkhjhjsffsdjhlkslfhdsfkljhdfjknkjbnkjsnmnc jdfkn jdjnj ndjnjd jdjdcjdncjdn jdhsjkdcndknjckndojnvkcn jfvnjcn jfjjjfjhhgfjdkflkdfhlshgglksdhfjnvjdklkgdghkjdssskkhshjffhnghfjhdjdnnvnjvvjnnvnvnvvv=ccccccjcjjcjjjhdkhdkhskhdfhdskfnfccufiecnekhhucf
vc
c
c
c
c
c
c
c
c
c
c
c
c
cc
c
c
cc
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
c
\(=\dfrac{y\left(5x+y^2\right)-x\left(5y-x^2\right)}{x^2y^2}\)
\(=\dfrac{5xy+y^3-5xy+x^3}{x^2y^2}\)
\(=\dfrac{y^3+x^3}{x^2y^2}\)
1) 2x + 2y - x(x+y)
= 2(x + y) - x(x + y)
= (2 - x)(x + y)
2/ 5x2 - 5xy -10x + 10y
= 5x(x - y) - 10(x - y)
= (5x - 10(x - y)
3/ 4x2 + 8xy - 3x - 6y
= 4x(x + 2y) - 3(x + 2y)
= (4x - 3)(x + 2y)
1) 2x + 2y - x(x + y)
= 2(x + y) - x(x + y)
= (2 - x)(x + y)
2) 5x2 - 5xy - 10x + 10y
= 5x(x - y) - 10(x - y)
= (5x - 10)(x - y)
= 5(x - 2)(x - y)
3) 4x2 + 8xy - 3x - 6y
= 4x(x + 2y) - 3(x + 2y)
= (4x - 3)(x + 2y)
4) 2x2 + 2y2 - x2z + z - y2z - 2
= 2(x2 + y2 - z(x2 + y2) - (2 - z)
= (2 - z)(x2 + y2) - (2 - z)
= (2 - z)(x2 + y2)
5) x2 + xy - 5x - 5y
= x(x + y) - 5(x + y)
= (x - 5)(x + y)
6) x(2x - 7) - 4x + 14
= x(2x - 7) - 2(2x - 7)
= (x - 2)(2x - 7)
7)x2 - 3x + xy - 3y
= x(x + y) - 3(x + y)
= (x - 3)(x + y)
a) Xem lại đề
b) x³ - 4x²y + 4xy² - 9x
= x(x² - 4xy + 4y² - 9)
= x[(x² - 4xy + 4y² - 3²]
= x[(x - 2y)² - 3²]
= x(x - 2y - 3)(x - 2y + 3)
c) x³ - y³ + x - y
= (x³ - y³) + (x - y)
= (x - y)(x² + xy + y²) + (x - y)
= (x - y)(x² + xy + y² + 1)
d) 4x² - 4xy + 2x - y + y²
= (4x² - 4xy + y²) + (2x - y)
= (2x - y)² + (2x - y)
= (2x - y)(2x - y + 1)
e) 9x² - 3x + 2y - 4y²
= (9x² - 4y²) - (3x - 2y)
= (3x - 2y)(3x + 2y) - (3x - 2y)
= (3x - 2y)(3x + 2y - 1)
f) 3x² - 6xy + 3y² - 5x + 5y
= (3x² - 6xy + 3y²) - (5x - 5y)
= 3(x² - 2xy + y²) - 5(x - y)
= 3(x - y)² - 5(x - y)
= (x - y)[(3(x - y) - 5]
= (x - y)(3x - 3y - 5)
\(\dfrac{5x+y^2}{x^2y}-\dfrac{5y+x^2}{xy^2}\)
\(=\dfrac{y\left(5x+y^2\right)}{x^2y^2}-\dfrac{x\left(5y-x^2\right)}{x^2y^2}\)
\(=\dfrac{5xy+y^3}{x^2y^2}-\dfrac{5xy+x^3}{x^2y^2}\)
\(=\dfrac{5xy+y^3-5xy+x^3}{x^2y^2}\)
\(=\dfrac{\left(5xy-5xy\right)+x^3+y^3}{x^2y^2}\)
\(=\dfrac{x^3+y^3}{x^2y^2}\)
\(\dfrac{5x+y^2}{x^2y}-\dfrac{5y-x^2}{xy^2}=\dfrac{y\left(5x+y^2\right)}{y\cdot x^2y}-\dfrac{x\left(5y-x^2\right)}{x\cdot xy^2}\)
\(=\dfrac{5xy+y^3-5xy+x^3}{x^2y^2}=\dfrac{x^3+y^3}{x^2y^2}\) \(\left(x,y\ne0\right)\)